Leprosus i księżna. Pielęgnacja zakaźnie chorych w świetle dokumentów z procesu kanonizacyjnego św. Elżbiety Węgierskiej - Puchalska-Dąbrowska, Bernadetta (Tematy i Konteksty, 2021)
The aim of the article is to present the image of the care of infectiously ill in the light of the canonization process of St. Elizabeth of Hungary (1207-1231). The material under discussion includes testimonies made by the saint's spiritual director Conrad of Marburg and her four handmaids. The accounts made by direct observers of the duchess' life emphasize the variety of forms of her involvement in the care of lepers and those suffering from diseases that cause similar symptoms.